Evaluasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) pada Instalasi Rekam Medis Rumah Sakit di Kabupaten Demak Menggunakan Model Hot-Fit - Raharjo, Tuhfa Tamhidatunnisa; Wulandari, Fitria; Kurniadi, Arif (Politeknik Negeri Jember, 2024)
The implementation of SIMRS supports the smooth running of all activities at X Hospital, Demak Regency. There were several complaints that officers felt regarding network disturbances that occurred as a result of interfering with officer performance. The purpose of this study was to determine the success rate of SIMRS at x Hospital, Demak Regency through SIMRS evaluation using the HOT-FIT model. This research method is descriptive research with a quantitative approach. Data collection was carried out by distributing questionnaires to all medical record installation staff as respondents according to the inclusion and exclusion criteria. The results of the study obtained 38 respondents from the Medical Record Installation of Hospital, Demak Regency. The data is processed using Microsoft Excel. The results of the study stated that in the Human component officers were satisfied with system performance (77.6%) in terms of system use and user satisfaction, SIMRS had important information that made it easier for officers to provide services to patients. From an organizational point of view, the system can integrate one sub-section with another (76.2%), as evidenced by the ease with which officers obtain the necessary patient data. And in the Technology component, SIMRS applies an information technology strategy in its development (76.7%) so that there is guaranteed protection in the management of systems that support the needs of up to date patient information.